(untitled) (Bangladesh Journal of Pharmacology, 2017)
The objective of current study was to evaluate the nephroprotective and nephrocurative effects of methanolic extract of Cestrum nocturnum leaves in rabbits. Gentamicin (80 mg/kg/day) was administered intramuscularly to induce nephrotoxicity. The induction was assessed by biochemical and histopathological analysis. Methanolic extract (100, 300 or 500 mg/kg) was given orally with gentamicin for 25 days in nephroprotective study whereas in nephrocurative study, gentamicin was administered intramuscularly for first 10 days and for next 15 days only methanolic extract (100, 300 or 500 mg/kg, orally) was administered. A significant decrease was found in total oxidant status, blood urea nitrogen, serum creatinine and uric acid levels whereas albumin level increased significantly. Histopathological studies also revealed nephroprotective and nephrocurative effects. In conclusion, the methanolic extract of C. nocturnum leaves exhibited significant nephro-protective and nephrocurative effects in experimental animal. Video Clip of Methodology: 6 min 47 sec: Full Screen Alternate